New perspectives in the regulation of hepatic glycolytic and lipogenic genes by insulin and glucose: a role for the transcription factor sterol regulatory element binding protein-1c - Foufelle, Fabienne; Ferré, Pascal (Biochemical journal, 2002)
The regulation of hepatic glucose metabolism has a key role in whole-body energy metabolism, since the liver is able to store (glycogen synthesis, lipogenesis) and to produce (glycogenolysis, gluconeogenesis) glucose. These pathways are regulated at several levels, including a transcriptional level, since many of the metabolism-related genes are expressed according to the quantity and quality of nutrients. Recent advances have been made in the understanding of the regulation of hepatic glycolytic, lipogenic and gluconeogenic gene expression by pancreatic hormones, insulin and glucagon and glucose. Here we review the role of the transcription factors forkhead and sterol regulatory element binding protein-1c in the inductive and repressive effects of insulin on hepatic gene expression, and the pathway that leads from glucose to gene regulation with the recently discovered carbohydrate response element binding protein. We discuss how these transcription factors are integrated in a regulatory network that allows a fine tuning of hepatic glucose storage or production, and their potential importance in metabolic diseases.